(3QSGdI aj EKHGJ GdaQb Hjf NWGH GdJcdja hNWGH GdhVYs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3YHO GdbGOQ Hf eMeO Hf jYbhHs)
(3ChdgG (B:s
(3HYO GdMeOdI hGdJUdjI (B: (3hHYO aEf GdJejJ efj CjVG GdaQb Hjf NWGH GdJdcdja hNWGH GdhVY aGYde hdOj HGQc Gddg ajce hdce Cf GdMce ef MjK gh EKHGJ CeQ dCeQ Ch fajg Yfg aEfg cGf GdMGce GdYGOI Cj GdJLQHI hGdJcQGQ Sej GdYGOj hMOg hEKHGJ GdQHW Hjf CeQ hBNQs
(3BNQgG (B:s
(3aEPG fXQJ dchf gPg GdNeSI JLQj eY cd hGMO ef GdCMcGe GdNeSI cGfJ GdLedI NeSI hYTQjf aGjVI ef VQH NeSI aj eKdgG hJhVjM Pdc jWdH ef GdeWhdGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds